Leaf-litter breakdown as a tool to assess the functional integrity of high Andean streams of Southern Ecuador - Rincon, Jose (2017)
The ecological condition of tropical Andean rivers are threatened by many human activities including changes in land use and cover in watersheds. Current protocols diagnose the structural condition of streams but not their function. In this study we proposed an assessment tool using the leaf-litter breakdown as a measure of the functional condition and health of high Andean streams in Southern Ecuador, including methodology and threshold values adapted to local conditions. We selected 15 streams in three micro-basins (Mazán, Llaviuco and Matadero) within or in the vicinity of Cajas National Park where we deployed litterbags for 15, 28 and 64 days. We used two types of mesh (coarse and fine) for the litterbags in order to separate the contribution of macro-invertebrates and microorganisms in the decomposition process and also tested two different leaf substrates: Alder (Alnus acuminata) and Miconia (Miconia bracteolata). In each collection period we determined physical and chemical parameters, applied the riparian quality index (QBR-And) and river habitat index (IHF). Decomposition rates (-k) were determined from the time period at which approximately 50 % ash-free mass would have been lost. We used Ktotal and the ratio of the rate of decomposition between coarse and fine mesh (Kg/Kf) to define the functional condition thresholds. To test the metrics sensitivity we used graphical methods, one-way ANOVA and discriminative efficiency (ED). The analysis of watershed land-use and cover showed a gradient of intervention: Matadero ≥ Llaviuco > Mazán. The composition of the environmental variables of Mazán streams were different with respect to Llaviuco and Matadero, whose values were similar to each other. The QBR-And index showed a significant gradient from very low levels in Matadero (27.5), moderately high values in Llaviuco (66.5) to high values in Mazán (87). Alder leaf-litter breakdown rates were significantly faster in Mazán than in Matadero and Llaviuco streams, while breakdown rates of Miconia were not significantly different among watersheds. The Kg/Kf ratio was significantly higher in Mazán compared to Llaviuco and Matadero, which did not differ. We consider the Kg/Kf metric sensitive enough to discriminate impacts in the studied areas. Our results support the use of the leaf-litter breakdown as an appropriate tool to assess functional ecological condition, complementing the structural assessments of these Andean rivers.